Praktek Ayat-Ayat Kauniyah: Persepsi Pemahaman Al-Qur`an Sebagai Sumber Ilmu Pengetahuan Melalui Pendalaman Integrasi Islam dan Sains - Muhammad Rayfansyah; Zarkasih; Rian Vebrianto (Journal of Practice Learning and Educational Development, 2026)
This study aims to examine students’ perceptions and understanding of kauniyah verses in the Qur’an as a source of knowledge through the integration of Islam and science. The methodology employed in this research is a mixed methods approach with an explanatory sequential design, in which quantitative data are collected and analyzed first, followed by qualitative data to further explain and deepen the findings. The study involved 30 participants aged approximately 20–25 years. The research instruments consisted of a questionnaire and interviews. All instrument items were declared valid, with r-count values greater than r-table (0.361), and reliable, with a Cronbach’s Alpha coefficient of 0.951. Data were collected through the distribution of questionnaires via Google Forms and direct field observations. Data analysis was conducted using data triangulation techniques. The results of descriptive statistical analysis indicate that students’ perceptions fall into a very high category, with a mean score of 4.44. In addition, the average total respondent score reached 70.97 or 88.7%, indicating a strong dominance of positive perceptions toward the Qur’an as a source of knowledge. These findings suggest that students possess a good level of understanding and a positive attitude toward the integration of Islam and science in the learning context.